Social cost and benefits of patent protection for medicines: Case of Indonesian seaweeds hard capsule invention - RAHMAH, M (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Seaweeds become natural medicinal sources. This essay aims at discussing the patent protection of seaweeds for medication. To achieve the goal, this essay will firstly describe the importance of seaweeds for medication and their prospects, before analyzing the patenting of seaweeds for medicines. It also reviews substantial social costs and benefits of seaweeds patent protection for medicines and suspects that patent on the innovation of medicines might turn a miracle into a social tragedy. The paper recommends the effective balance between the public interest and the legitimate private interest of patent holders and averts the perception of prioritization of private rights over public health.